Management of Academics – Problems and Challenges from the Perspective of Transaction Cost Economics - Pietrzak, Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Human resources, namely potential of employee’s knowledge, skills and engagement became the key factor in the contemporary economy. This is particularly true in the case of knowledge workers – those with high degrees of expertise, education or experience who are doing highly knowledge intensive jobs. In fact, academics are archetypes of such employees. The paper concerns with the problem of difficulties in detailed defining efforts’ standard in the case of academics. Academics have to invest in assets, which are specific to the relation with employer, also high informational asymmetry plagued their job. Thus, there are high transaction costs involved in the exchange under employment relation umbrella in the higher education. Therefore, some safeguards are needed like long‑term stable employment. There is also the problem of writing ex ante complete contracts as well as monitoring and accountability of researchers work. One of the solution of this problem could be relational contracting rooted in trust and cooperation between sides of the employment relations. Often, so called psychological contracts are embedded in those relations. However, we observe recently in Poland attempts (according to the reforms of higher education sector) of introducing some kind of piece‑rate incentive systems, where piece‑rate means “production” of scientific publications. This is form of departure from traditional model of the university. Such departure could be seen by many academicians as breaching of psychological contract involved in their employment relation, and as such could be counterproductive.